2010
DOI: 10.1128/iai.00893-09
|View full text |Cite
|
Sign up to set email alerts
|

A Thiolase of Mycobacterium tuberculosis Is Required for Virulence and Production of Androstenedione and Androstadienedione from Cholesterol

Abstract: Mycobacterium tuberculosis, the causative agent of tuberculosis, is an intracellular pathogen that shifts to a lipid-based metabolism in the host. Moreover, metabolism of the host lipid cholesterol plays an important role in M. tuberculosis infection. We used transcriptional profiling to identify genes transcriptionally regulated by cholesterol and KstR (Rv3574), a TetR-like repressor. The fadA5 (Rv3546) gene, annotated as a lipidmetabolizing thiolase, the expression of which is upregulated by cholesterol and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
274
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 190 publications
(286 citation statements)
references
References 35 publications
10
274
2
Order By: Relevance
“…Moreover, the expression level of the Rv1106c gene is similar to that of the preceding xseAB genes (Nesbitt et al, 2010), reinforcing the hypothesis that all these genes form part of the same operon. The short distance (9 bp) between the stop codon of xseB and the start codon of the Rv1106c gene in M. tuberculosis also precludes the existence of a transcription terminator in this region.…”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…Moreover, the expression level of the Rv1106c gene is similar to that of the preceding xseAB genes (Nesbitt et al, 2010), reinforcing the hypothesis that all these genes form part of the same operon. The short distance (9 bp) between the stop codon of xseB and the start codon of the Rv1106c gene in M. tuberculosis also precludes the existence of a transcription terminator in this region.…”
Section: Discussionsupporting
confidence: 52%
“…Moreover, transcriptomic analyses have demonstrated that the Rv1106c gene is expressed at the same level in the wildtype strain as in a completely derepressed KstR mutant of M. tuberculosis (Nesbitt et al, 2010). Moreover, the expression level of the Rv1106c gene is similar to that of the preceding xseAB genes (Nesbitt et al, 2010), reinforcing the hypothesis that all these genes form part of the same operon.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Metabolites with a C 5 side chain have not been reported to accumulate during growth on cholesterol. Furthermore, degradation of the cholesterol side chain is predicted to proceed via thiolytic cleavage, yielding a C 5 CoA thioester intermediate not requiring activation (47). Consistent with this prediction, FadD17 does not appear to be essential for growth of M. tuberculosis on cholesterol (31).…”
Section: Discussionsupporting
confidence: 66%
“…The cholesterol catabolic pathway of Mtb is very similar to that of other pathogenic and environmental actinomycetes (10), as initially predicted in Rhodococcus jostii RHA1 (5). Sidechain degradation is initiated by a cytochrome P450 and proceeds via a ␤-oxidative process (11).…”
mentioning
confidence: 68%